Six similar sequential ruptures of the San Andreas fault, Carrizo Plain, California - Liu, Jing (2013)
We document the precise sizes, but not the dates, of the six latest offsets across the San Andreas fault at Wallace Creek, California. Three and perhaps four of these, including the latest in 1857, show dextral offset of 7.5–8 m. The third and fourth offsets, however, are just 1.4 and 5.2 m. The predominance of similar offsets for the latest six events suggests that the fundamental properties of the fault system that control slip size do not vary greatly from event to event. The large offsets imply that ruptures involving this site are typically more than 200 km long.